Reactivity of Seven-Membered-Ring trans-Alkenes with Electrophiles - Sanzone, Jillian R.; Woerpel, K. A. (Synlett, 2017)
Seven-membered-ring trans-alkenes containing a silicon–oxygen bond reacted rapidly with oxygen gas and electron-deficient alkenes and alkynes to give products with high selectivity. Addition of an electron-donating substituent or incorporating additional strain increased the reactivity by over two orders of magnitude. These results indicate that release of strain is not the only driving force for reactivity.
Keywords: alkenes; conjugate addition; cycloheptene; strained molecules; silicon